2009
DOI: 10.1001/archfacial.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Incision Closures With Subcuticular and Percutaneous Staples

Abstract: Subcuticular staples represent a safe, comfortable, and potentially more rapid alternative to percutaneous staples. Modifications of the subcuticular stapler device are required before its full potential can be realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The use of absorbable material precludes the need to remove the staples, which in terms of metallic staple removal, can be both painful to the horse and dangerous to the veterinarian. There is also no reported discomfort associated with the presence of the SAS in human patients, even in areas with delicate skin coverage under tension (Dresner and Hilger ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of absorbable material precludes the need to remove the staples, which in terms of metallic staple removal, can be both painful to the horse and dangerous to the veterinarian. There is also no reported discomfort associated with the presence of the SAS in human patients, even in areas with delicate skin coverage under tension (Dresner and Hilger ).…”
Section: Discussionmentioning
confidence: 99%
“…[113] INSORB has been extensively studied and was clinically proven to offer substantial benefits to patients of different procedures including obstetric, orthopedic, transplant, plastic, and colorectal surgery. [112] A number of studies observe benefits such as [114][115][116][117] : (i) lower incidence of infection and other complication, (ii) reduced operative time, (iii) less patient discomfort and decreased analgesic use, and (iv) excellent cosmetic result. Even veterinary medicine appears to benefit from the use of subcuticular absorbable staples (SAS).…”
Section: Zinc As Absorbable Staplementioning
confidence: 99%
“…Limb incisions were also difficult due to the inadequate amount of subcuticular space, which is needed for the slight eversion of the skin after staple attachment. Dresner and Hilger [115] similarly reported difficulty in the accurate placement of the staples in scalp surgery due to the relatively thin dermal layer in this region. They thus suggested that modifications may be necessary for the subcuticular stapler to address these difficulties during scalp surgeries.…”
Section: Zinc As Absorbable Staplementioning
confidence: 99%
“…Skin staples are also fast and easy to apply, but removal can be painful and are also more expensive than sutures. [1][2][3] In this contest authors thought of interrupted absorbable subcuticular sutures where authors can tackle the above mentioned limitations; while actually reducing the financial burden of the patients since the same sutures used for subcutaneous sutures can be used for subcuticular sutures also. Aims and objectives of the study were to compare the interrupted absorbable subcuticular sutures and conventional wound closure techniques in surgeries for benign breast diseases.…”
Section: Introductionmentioning
confidence: 99%